2010
DOI: 10.1007/s10151-010-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of local anesthetics in preventing postoperative adhesions in rat models

Abstract: Prilocaine and bupivacaine were found to decrease the severity of intra-peritoneal adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The quality of adhesions in the control group was significantly higher in comparison with that in the lidocaine 2% (6 mg/kg), bupivacaine and normal saline groups, and higher in the lidocaine 6 mg/kg group than in the bupivacaine group. In contrast, Ozturk et al (19) showed that the quality and quantity of adhesions in all groups were similar (P > 0.05). Perhaps one of the main reasons for this difference was the differences in dosages of the drugs.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The quality of adhesions in the control group was significantly higher in comparison with that in the lidocaine 2% (6 mg/kg), bupivacaine and normal saline groups, and higher in the lidocaine 6 mg/kg group than in the bupivacaine group. In contrast, Ozturk et al (19) showed that the quality and quantity of adhesions in all groups were similar (P > 0.05). Perhaps one of the main reasons for this difference was the differences in dosages of the drugs.…”
Section: Discussionmentioning
confidence: 81%
“…Local anaesthetic drugs have recently been considered in this field. In a few studies using these drugs, satisfactory results have been reported (18,19). However, there is clearly a lack of adequate information in this area and further studies are needed to confirm the results and optimal usage of other drugs.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…[4][5][6] Many adjuvants that prevent inflammation (steroidal and non-steroidal anti-inflammatory medications), degrade fibrin (recombinant tissue plasminogen activator [t-PA]), or act as barriers (absorbable material/ solution/gel or liquid paraffin) have been evaluated to prevent post-surgical adhesions. [7][8][9] Nevertheless, no definitive method or agent has been proven to prevent the formation of post-surgical adhesions.…”
Section: Introductionmentioning
confidence: 99%